2008
DOI: 10.1308/147363508x260050
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the EWTD on surgical SpRs: a regional survey

Abstract: The implementation of the European Working Time Directive (EWTD) has changed the way surgical training is delivered in the European Union. The Jaeger ruling by the European Court of Justice states that health service employers must guarantee an 11-hour rest period within any 24-hour time period, while the SiMAP ruling has enshrined the concept of all time spent at work being classified as working time. To comply with these rulings, as of August 2004 most NHS Trusts across the UK have implemented shift systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“… 26–28 These strong assertions are, without exception, based on opinions, anecdotes or non-validated questionnaires and surveys. 29–32 Our study is the first objective assessment of the impact of 2009 EWTD-compliant schedules on patient care, the primary concern of healthcare providers, and presents scientific evidence upon which to begin basing policy decisions.…”
Section: Discussionmentioning
confidence: 99%
“… 26–28 These strong assertions are, without exception, based on opinions, anecdotes or non-validated questionnaires and surveys. 29–32 Our study is the first objective assessment of the impact of 2009 EWTD-compliant schedules on patient care, the primary concern of healthcare providers, and presents scientific evidence upon which to begin basing policy decisions.…”
Section: Discussionmentioning
confidence: 99%
“…7 Another study reported an overwhelming majority (91%) wishing to work 'on call' as opposed to doing shifts and 96% agreed that the on-call system was better for training, implying a decrease in the quality of training opportunities. 8 Other implications include a reduction in trainer-trainee interaction, lack of continuity of patient care and a negative effect on trainee wellbeing and quality of life. 2 Most trainees are committed to their surgical training and do not want their working hours to be limited to a 48hour week although they clearly wish to be trained to be safe and competent surgeons.…”
Section: ) Discussionmentioning
confidence: 99%